Prevention of Cyclophosphamide-Induced Immunosuppression in Mice With Traditional Chinese Medicine Xuanfei Baidu Decoction - Yan, Huimin; Lu, Jia; Wang, Jiabao; Chen, Lu; Wang, Yu; Li, Lin; Miao, Lin; Zhang, Han (Frontiers in Pharmacology, 2021)
Background and aims: Traditional Chinese Medicine Xuanfei Baidu Decoction (XFBD) was designed and successfully applied for COVID-19 disease treatment in China, while the mechanism is still not clear. Methods: To evaluate the protective effect of XFBD on immunosuppression in cyclophosphamide (CY)-treated mice, XFBD was orally administrated and the body weight was measured and the immune organ index was calculated. HE staining was performed to analysis the pathological structures of liver, spleen and thymus. The levels of cytokines and immunoglobulin in serum and spleen were evaluated by ELISA and RT-PCR. Splenic lymphocytes were isolated and LPS-stimulated cell proliferation and number of CD4+ and CD8+ T lymphocytes were evaluated. Results: XFBD significantly suppressed body weight loss and increased the indices of spleen and thymus. The pathological alteration was much improved after XFBD administration. The reductions of TNF-α, IFN-γ, IgG and IgM levels in serum and IL-2, IL-4, and IL-6 expressions in spleen were all significantly alleviated by XFBD. Splenic lymphocyte proliferation in response to LPS was further enhanced after treatment with XFBD. The reduction of CD4+ and CD8+ T lymphocytes in CY-treated mice were also highly increased in XFBD groups. Conclusion: Our ﬁndings suggested that XFBD played a crucial role in protection against immunosuppression in CY-treated mice and could be a potential candidate for immune modification and therapy.